Adoptive transfer of ex vivo expanded Vγ9Vδ2 T cells in combination with zoledronic acid inhibits cancer growth and limits osteolysis in a murine model of osteolytic breast cancer. (1st February 2017) - Zysk, Aneta; DeNichilo, Mark O.; Panagopoulos, Vasilios; Zinonos, Irene; Liapis, Vasilios; Hay, Shelley; Ingman, Wendy; Ponomarev, Vladimir; Atkins, Gerald; Findlay, David; Zannettino, Andrew; Evdokiou, Andreas
Abstract: Bone metastases occur in over 75% of patients with advanced breast cancer and are responsible for high levels of morbidity and mortality. In this study, ex vivo expanded cytotoxic Vγ9Vδ2 T cells isolated from human peripheral blood were tested for their anti-cancer efficacy in combination with zoledronic acid (ZOL), using a mouse model of osteolytic breast cancer. In vitro, expanded Vγ9Vδ2 T cells were cytotoxic against a panel of human breast cancer cell lines, and ZOL pre-treatment further sensitised breast cancer cells to killing by Vγ9Vδ2 T cells. Vγ9Vδ2 T cells adoptively transferred into NOD/SCID mice localised to osteolytic breast cancer lesions in the bone, and multiple infusions of Vγ9Vδ2 T cells reduced tumour growth in the bone. ZOL pre-treatment potentiated the anti-cancer efficacy of Vγ9Vδ2 T cells, with mice showing further reductions in tumour burden. Mice treated with the combination also had reduced tumour burden of secondary pulmonary metastases, and decreased bone degradation. Our data suggests that adoptive transfer of Vγ9Vδ2 T cell in combination with ZOL may prove an effective immunotherapeutic approach for the treatment of breast cancer bone metastases. Highlights: Immunotherapy using cytotoxic Vγ9Vδ2 T cells is gaining momentum as a novel therapeutic approach for the treatment of solid and haematological malignancies. Vγ9Vδ2 T cells localise to breast cancer lesions in the bone and multiple Vγ9Vδ2 T cell infusions decrease tumour burden and lung metastases. ZOL pre-treatment potentiates the anti-cancer efficacy of Vγ9Vδ2 T cells and decreases tumour-associated bone loss. Adoptive transfer of Vγ9Vδ2 T cells in combination with ZOL may be beneficial in patients with advanced breast cancer.